A Comprehensive Database of CGIAR Climate-Related Journal Articles (2012–2023) - Orth, Alan S.; Bosire, Caroline K.; Rabago, Laura; Vaidya, Shrijana; Rajbhandari, Sitashma; Pradhan, Prajal; Mukherji, Aditi (International Livestock Research Institute, 2024)
This dataset contains bibliographic metadata for 3,450 peer-reviewed journal articles used in the 2024 synthesis of CGIAR work on climate change. The metadata was retrieved from eight CGIAR institutional repositories, processed using a Python-based extract, transform, and load (ETL) pipeline, and screened for climate change relevance in Rayyan.